Perubahan Sosial Ekonomi sebagai Dampak dari Pariwisata Taman Nasional Tanjung Puting (Studi Kasus di Kelurahan Kumai Hulu Kecamatan Kumai Kabupaten Kotawaringin Barat) - Ise Afitah; Mariaty Mariaty; Arifin Arifin (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to identify social changes that occur and map various economic benefits of the tourism potential of Tanjung Puting National Park (TNTP). For the people of Kelurahan Kumai Hulu. The benefits of this study are expected to provide information for relevant agencies for the development of TNTP tourism planning and management. There are socio-economic changes that occur to the people of Kumai Hulu, Kumai Sub-district, West Kotawaringin Regency due to the existence of TNTP tourism. Social changes are marked by the awareness of association or grouping in the Kumai community. There are two community associations, namely the Klotok Wisata Kumai Association and the Indonesian Tour Guide Association. Some values shift in the city due to tourism, before around Kumai Hulu many liquor and stall shops were young people who often gathered and drank. Where the needs and demands of tourism conditions are increasingly more significant, foreign tourists make working people start learning foreign languages, for example, Mr. Arsyad who is only a klotok worker until he becomes a guide, by self-taught with direct tourists. Aware of Kumai's public education by referring to choosing education about tourism. Some values shift in the community due to tourism, before around Kumai Hulu many liquor and stall shops were young people who often gathered and drank. Where the needs and demands of tourism conditions are increasingly higher, foreign tourists make working people start learning foreign languages.